1985
DOI: 10.1073/pnas.82.1.253
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible spongiform encephalopathy in the gray tremor mutant mouse.

Abstract: Gray tremor (gt) is an autosomal recessive mutation in the mouse linked to caracul (Ca) on chromosome 15. The complex mutant phenotype includes pigmentation defects, tremor, seizures, hypo-and dysmyelination in central and peripheral nervous systems, spongiform encephalopathy, and early death. The heterozygote (+/gt) is phenotypically normal but develops a mild spongiform encephalopathy from 2 months of age onward. The pigmentation and myelination disorders indicate that the gt genetic locus is active neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…Scrapie is transmissible in its entirety: host animals develop the characteristic clinical syndrome and neuropathology. Previous work on the GT mutant demonstrated that the pathological changes characteristic of the homozygote could be transmitted to genotypically normal mice after an incubation period as long as 2 years (Sidman et al, 1985). Mice inoculated with gt/gt brain homogenates did not develop a clinical syndrome resembling that of either the gt/gt homozygote or scrapie (Sidman et al, 1985;Hoffman et al, 1987).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Scrapie is transmissible in its entirety: host animals develop the characteristic clinical syndrome and neuropathology. Previous work on the GT mutant demonstrated that the pathological changes characteristic of the homozygote could be transmitted to genotypically normal mice after an incubation period as long as 2 years (Sidman et al, 1985). Mice inoculated with gt/gt brain homogenates did not develop a clinical syndrome resembling that of either the gt/gt homozygote or scrapie (Sidman et al, 1985;Hoffman et al, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…Mice homozygous for the grey tremor (GT) trait (gt/gt) display a characteristic pigmentation of their coats, seizures, tremors, ataxia and death by 90 days of age (Sidman et al, 1985). The neuropathology is a non-inflammatory spongiform appearance to the brain (Kinney & Sidman, 1986) resembling that of the transmissible spongiform diseases scrapie and Creutzfeldt-Jakob disease (CJD).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations